2015
DOI: 10.1039/c4py01664e
|View full text |Cite
|
Sign up to set email alerts
|

Semi-crystalline diblock copolymer nano-objects prepared via RAFT alcoholic dispersion polymerization of stearyl methacrylate

Abstract: nano-objects prepared via RAFT alcoholic dispersion polymerization of stearyl methacrylate. Polymer Chemistry, 6 (10). pp. 1751 -1757 . ISSN 1759 https://doi.org/10.1039/c4py01664e eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…For example, Charleux and co-workers conducted the RAFT dispersion polymerization of a bespoke cholestryl-based (meth)acrylic core-forming monomer in an ethanol/water mixture to produce well-defined diblock copolymer nanorods and nanofibers [44]. Similarly, Armes and coworkers conducted the RAFT dispersion polymerization of stearyl methacrylate (SMA) in pure ethanol using a PDMA macro-CTA (Figure 2c) [86]. The latter approach yielded PDMA-PSMA spheres, worms or vesicles with semi-crystalline stearyl side-chains in the PSMA core-forming block [86].…”
Section: 4alternative Core-forming Blocks For Raft Alcoholic Dispementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Charleux and co-workers conducted the RAFT dispersion polymerization of a bespoke cholestryl-based (meth)acrylic core-forming monomer in an ethanol/water mixture to produce well-defined diblock copolymer nanorods and nanofibers [44]. Similarly, Armes and coworkers conducted the RAFT dispersion polymerization of stearyl methacrylate (SMA) in pure ethanol using a PDMA macro-CTA (Figure 2c) [86]. The latter approach yielded PDMA-PSMA spheres, worms or vesicles with semi-crystalline stearyl side-chains in the PSMA core-forming block [86].…”
Section: 4alternative Core-forming Blocks For Raft Alcoholic Dispementioning
confidence: 99%
“…Similarly, Armes and coworkers conducted the RAFT dispersion polymerization of stearyl methacrylate (SMA) in pure ethanol using a PDMA macro-CTA (Figure 2c) [86]. The latter approach yielded PDMA-PSMA spheres, worms or vesicles with semi-crystalline stearyl side-chains in the PSMA core-forming block [86]. Potential advantages for such nano-objects could be the preparation of relatively stiff worms of tunable flexibility and perhaps also vesicles with less permeable membranes, thus offering enhanced encapsulation efficiency.…”
Section: 4alternative Core-forming Blocks For Raft Alcoholic Dispementioning
confidence: 99%
“…[44][45][46] Lansalot and Carlmark 38 conducted RAFT emulsion polymerization based on the PISA process to obtain spherical particles comprising P(DMAEMA-stat-MAA)-b-PMMA, and Armes and coworkers reported synthesis of spherical particles of poly(2-(dimethylamino)ethyl methacrylate-b-stearyl methacrylate) (PDMAEMA-b-PSMA) via RAFT dispersion polymerization in ethanol. 37 Despite the potential of tuning the charge density of P(DMAEMA) by adjustment of the pH, to the best of our knowledge there are no precedents of exploiting this property to tune the PISA particle morphology beyond spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nanoparticles comprising block copolymers with cationic, 28,34,[36][37][38] anionic 25,39,40 and zwitterionic 41,42 character have been synthesised via PISA. In both dispersion and emulsion-based PISA systems, it has been shown that the morphology is influenced by the charge density of the solvophilic block -if the charge density is too high, only spheres can form due to the strong repulsive forces between the chains on decreasing the curvature of the interface between the core and the continuous phase.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] Pan and co-workers have made a number of notable contributions to the field of RAFT alcoholic dispersion polymerisation [37][38][39][40]. Their approach typically involves chain extension of a soluble macro-CTA such as poly(2-dimethylaminoethyl methacrylate) with styrene in methanol [37].…”
Section: Introductionmentioning
confidence: 99%